Детское погребение на могильнике черняховской культуры Войтенки - Шультце, Э.; Любичев, М.В.; Козак, А.Д. (Археологія і давня історія України, 2020)
Отдельная публикация материалов детского
погр. 231 могильника Войтенки с археологическим
и антропологическим анализом является важной,
ибо этот комплекс отличается особенностями
инвентаря, позволяющих исследовать социальное
положение ребенка и его семьи. The children’s graves at the cemeteries of the Chernyakhiv
/ Sîntana de Mureş culture are the relevant
problem for the archaeology of the period. Children’s
burials at the cemeteries of this culture have been the
subject of special study for more than fifteen years. At
the cemetery Voytenky 15 graves of children of various
ages were discovered (graves 6, 34, 50, 72, 79, 85, 94,
97, 99, 103, 126, 217, 218, 220, 231). Their analysis is
envisaged within the framework of the project on the
reconstruction of the social structure of the population
of the Chernyakhiv culture on the basis of the cemetery
Voytenki.
The publication of materials from grave 231 of the
cemetery Voytenki includes archaeological and anthropological
analysis. Inventory features of the complex
allow determination of the social status of the child and
his family.
The burial’s inventory includes 24 vessels. A specific
feature of this complex is the presence of an amphora.
The burial belongs to the phase «C» after the
relative chronology of the «classical» Chernyakhiv culture
horizon in the Dnepr-Donetsk
forest-steppe (after
M. Lyubichev). This correlates with stages C3, C3/D1
by J. Tejral, and in absolute dates can be attributed to
the third quarter of the 4th century.
The age of the child determined as (1.5) 2—2.5 years.
Pathological lesions on the skeleton diagnosed as traces
of scurvy, probably anemia, and viral or bacterial
meningitis. Their presence permits raise the question
of adaptation of the children of particular social class
to their living conditions. Presumably, some adults of
this social stratum belonged to the mobile part of the
population or were in close contact with migrants. Migrations
could be seen as one of the reasons, led to the
emergence of new infections, which primarily affected
children.
The grave with the amphora testifies to the strong
economic position of the family, whose child was buried.
This family probably participated in an interregional
exchange. Дитячі поховання на могильниках культури Черняхів
/ Синтана-де-Муреш є актуальною проблемою
у археології та антропології. Дитячі поховання на могильниках
цієї культури вже понад п’ятнадцять років
є предметом спеціального вивчення. На могильнику
Війтенки відкрито 15 поховань дітей різного віку (поховання
6, 34, 50, 72, 79, 85, 94, 97, 99, 103, 126, 217,
218, 220, 231). Їх аналіз передбачено у межах проекту з
реконструкції соціальної структури носіїв черняхівської
культури могильника Війтенки. Публікація матеріалів
поховання 231 могильника Війтенки включає
археологічний та антропологічний аналіз. Особливості
інвентаря, які формують комплекс дозволяють визначити
соціальний стан дитини та її родини.
Інвентар поховання включає 24 посудини. Особливістю
цього керамічного комплексу є наявність
амфори. Поховання відноситься до фази «С» відносної
хронології горизонта «класичної» черняхівської
культури у дніпро-донецькому лісостепу (за М. Любичевим),
яка співвідноситься із ступенями С3, С3/
D1 Я. Тейрала. В абсолютних датах поховання може
бути датоване періодом до третьої чверті IV ст.
Вік дитини визначено як (1,5) 2—2,5 роки. Патологічні
ознаки на скелеті діагностовані як наслідки
цинги, імовірно анемії та вірусного або бактеріального
менінгіту. Їх присутність в цьому похованні дозволяє
поставити питання про адаптацію дітей певного
соціального класу до умов життя. Допускається, що
дорослі представники визначеного соціального стратуму
входили до мобільної частини популяції або ж
знаходились у тісному контакті з мігрантами. Міграції
можуть бути розглянуті як одна з причин появи нових
інфекцій, від яких в першу чергу страждали діти.
Поховання з амфорою свідчить про міцні господарські
позиції родини, дитина якої була похована. Ця родина
імовірно приймала участь у міжрегіональному обміні.